Detailed kinetic mechanism of gas-phase reactions of volatiles released from biomass pyrolysis. (October 2016) - Debiagi, Paulo Eduardo Amaral; Gentile, Giancarlo; Pelucchi, Matteo; Frassoldati, Alessio; Cuoci, Alberto; Faravelli, Tiziano; Ranzi, Eliseo
Abstract: Comprehensive chemical models to describe the behavior of biomass pyrolysis, gasification and combustion are crucial for the simulation and design of thermochemical processes of ligno-cellulosic materials. Despite this importance, reliable and predictive models are still not well known. The original aspect of this work is to present a comprehensive and predictive model of pyrolysis, gasification, and combustion, starting from biomass characterization, through the description of released volatiles at the particle scale, until the effect of the secondary gas-phase reactions at the reactor scale. All these aspects can play a relevant role in the biomass thermo-valorization processes. Most of released species from biomass devolatilization are oxygenated hydrocarbons. This study aims at identifying some reference rate parameters, based on analogy and thermochemistry rules, for the different reaction classes. Once rate rules are defined, they allow an easy extension to analogous compounds. In this way, the kinetic mechanism already developed for jet and diesel fuels is extended to the new tar species released by biomasses. Despite unavoidable approximations when the interest is also at the reactor scale, this model is the only one, to our knowledge, able to describe the whole process from biomass to final products, in a predictive and satisfactory way. Highlights: A predictive model of biomass pyrolysis, gasification, and combustion is discussed. A lumped approach to describe biomass pyrolysis products is presented. The role of successive reactions of tar components is investigated. Secondary gas phase reactions of released volatiles are analyzed. Generic rate rules for oxygenated species are highlighted.